OPTIMIZATION OF ALGORITHM AND SOFTWARE OF MATHEMATICAL MODEL OF GAS TURBINE ENGINE WORKING PROCESS - Якушенко, O. C. (Proceedings of National Aviation University (archive), 2021)
Methods of optimization of algorithm and software of mathematical models of working process of gas turbine engine are considered. The results of using these are givenmethods.